2021
DOI: 10.21037/tlcr-20-612
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of cribriform adenocarcinoma of the lung: validation analysis of 1,057 Japanese patients with resected lung adenocarcinoma and a review of the literature

Abstract: Background: Cribriform-predominant adenocarcinoma of the lung (Cribri-ADC) is a recently described tumor growth pattern. However, its prognostic impact has not been clearly determined. We analyzed the data of a series of 1,057 Japanese patients with resected lung adenocarcinoma to identify the clinical significance of Cribri-ADC.Methods: Cribriform pattern (Cribri-p) is defined as invasive back-to-back fused tumor glands with poorly formed glandular spaces or invasive tumor nests comprising tumors cells that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…If cribriform, signet‐ring solid and discohesive patterns were observed they were recorded separately from acinar or solid patterns. The cribriform was defined according to a previous report 15 . A signet‐ring solid pattern was defined as a type of solid pattern with abundant cytoplasmic mucin and eccentric nuclei in individual cells.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…If cribriform, signet‐ring solid and discohesive patterns were observed they were recorded separately from acinar or solid patterns. The cribriform was defined according to a previous report 15 . A signet‐ring solid pattern was defined as a type of solid pattern with abundant cytoplasmic mucin and eccentric nuclei in individual cells.…”
Section: Methodsmentioning
confidence: 99%
“…In the TMA cohort, the relationship between CK5 expression and gene alterations was investigated; 231, 230, 233, 149, 336 and 336 patients were analysed for EGFR , KRAS , BRAF and HER2 mutations and ALK and ROS1 rearrangements, respectively. The data of gene alterations were used from our previous studies 12,14,15,19–21 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For preoperative prediction, ground glass opacity (37), solid component (38,39) predominant pattern (38,(47)(48)(49) and solid-predominant pattern (47,48) are common in STAS. Nakajima et al (50) found that cribriform pattern was also related to STAS. At the genetic level (47), epidermal growth factor receptor (EGFR), tumor protein p53 (TP53), Kirsten rat sarcoma viral oncogene (KRAS), anaplastic lymphoma kinase (ALK), and ROS proto-oncogene 1 (ROS1) are the 5 most common changes in STAS-positive lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the poor prognosis when micropapillary and solid subtypes are present in a tumour is welldocumented, even as non-predominant subtypes [21][22][23][24][25][26]. It has been demonstrated that cribriform arrangements of tumour glands or complex glandular patterns, described within the acinar subtype of LADC, exhibit aggressive behaviour with poor prognosis [27,28]. Semiquantitative reporting of these subtypes is recommended in 5% increments to include even a small amount of prognostically significant subtypes [29].…”
Section: Introductionmentioning
confidence: 99%